War dances - Alexie, Sherman, 1966- (Grove Press, 2009)
With bright insight into the minds of artists, entrepreneurs, fathers, husbands, and sons, Alexie populates his stories with average men on the brink of exceptional change: In the title story, a son recalls his father<U+2019>s “natural Indian death” from alcohol and diabetes, just as he learns that he himself may have a brain tumor; “The Ballad of Paul Nonetheless,” dissects a vintage clothing store owner<U+2019>s failing marriage and courtship of a Puma-clad stranger in airports across the country; and “Breaking and Entering” recounts a film editor<U+2019>s fateful confrontation with an thieving adolescent. Brazen and wise War Dances takes us to the heart of what it means to be human. The new beginnings, successes, mistakes, and regrets that make up our daily lives are laid bare in this wide-ranging new work that is quintessential